An Integrative Interconnect Approach to Da’wa of Cak Nun to the Young Generation Indonesia - Basit, Abdul (International Conference of Moslem Society, 2018)
Da’wa approach among the younger generation is continues to develop along with the changing times and demands of the younger generation. The integrative interconnect da’wa approach was conducted by cak nun is one of the da'wa approaches that interesting and is loved by the young generation today. This approach as a new alternative to the existing approaches. Cak Nun has succeeded in drawing attention of young people from various regions with different characteristics. His expertise in word processing, packing messages, subjugating the mind, and entertaining the younger generation become the main attraction in da’wa of cak nun. Therefore, this paper will explains the new approach in da'wa is conducted by cak nun through integrative interconnect approach. Cak nun has done unification between verbal, intellectual, art, and cross cultural approaches and they was interconnected with Islam, Indonesia, and modernity. Then, This approach is realized in various methods of da'wa in accordance with the level of the needs of the young generation. Sometimes, Cak nun performs with kiyai kanjeng groups, love concessions, maiyah discussion groups, shalawatan, and even through social media. The philosophically and academically, da'wa of cak nun approach can be studied and developed within the framework of developing da'wa science, so that the integrative interconnect approach can be developed by the da'i and the wider community.